2018
DOI: 10.1111/joim.12863
|View full text |Cite
|
Sign up to set email alerts
|

Head trauma in sports – clinical characteristics, epidemiology and biomarkers

Abstract: Traumatic brain injury (TBI) is clinically divided into a spectrum of severities, with mild TBI being the least severe form and a frequent occurrence in contact sports, such as ice hockey, American football, rugby, horse riding and boxing. Mild TBI is caused by blunt nonpenetrating head trauma that causes movement of the brain and stretching and tearing of axons, with diffuse axonal injury being a central pathogenic mechanism. Mild TBI is in principle synonymous with concussion; both have similar criteria in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 96 publications
0
26
1
Order By: Relevance
“…Numerous studies have recently shown that changes in biomarkers that occur with SRC may be useful for both diagnosis determination and return-to-play decisions. 1,31,32 However, biomarker analysis typically requires invasive methods of collection, advanced laboratory processing, or advanced imaging, which limits its utility in most athletic settings (e.g., high schools). Furthermore, there is now evidence of brain injury in athletes who are asymptomatic or do not otherwise seek immediate clinical attention.…”
mentioning
confidence: 99%
“…Numerous studies have recently shown that changes in biomarkers that occur with SRC may be useful for both diagnosis determination and return-to-play decisions. 1,31,32 However, biomarker analysis typically requires invasive methods of collection, advanced laboratory processing, or advanced imaging, which limits its utility in most athletic settings (e.g., high schools). Furthermore, there is now evidence of brain injury in athletes who are asymptomatic or do not otherwise seek immediate clinical attention.…”
mentioning
confidence: 99%
“…The higher levels of p217 + tau seen in amyloid positive dementia subjects versus amyloid negative dementia subjects suggests the p217 + tau assays may be selective for AD, in contrast to total tau assays that detect high signal in many neurodegenerative conditions (e.g., after acute brain injury [20,21]). To further evaluate the potential of the p217 + tau assays to identify amyloid positive subjects, a second clinical cohort was examined, this time of presymptomatic subjects in order to observe a different range of A␤ 42 and A␤ 40 levels (n = 184 subjects, 79% amyloid positive).…”
Section: Csf P217 + Tau Is Superior To Traditional Tau Assays In Diffmentioning
confidence: 99%
“…Chronic Traumatic Encephalopathy (CTE) was formally known as Dementia Pugilistica or punch drunk because the condition was rst identi ed in boxers, and the symptoms resembled intoxication (Zetterberg et al, 2019). Dementia Pugilistica suggests a relationship between CTE and other dementias such as Alzheimer's disease.…”
Section: Chronic Traumatic Encephalopathymentioning
confidence: 99%